Clinical Implications of the New WHO Classification 2017 for Pituitary Tumors - Saeger, Wolfgang; Koch, Arend (Experimental and Clinical Endocrinology & Diabetes, 2021)
According to the WHO classification 2017 of Pituitary Tumors adenomas are classified not only by structure and immunostaining for pituitary hormones but also by expression of the pituitary transcription factors Pit-1, T-pit and SF-1. By these factors, three cell lineages can be identified: Pit-1 for the GH-, Prolactin- and TSH-cell lineage, T-pit for the ACTH-cell lineage, and SF-1 for the gonadotrophic cell lineage. By this principle, all GH and/or Prolactin producing and all TSH producing adenomas must be positive for Pit-1, all corticotrophic adenomas for T-pit, and all gonadotrophic for SF-1. In adenomas without expression of pituitary hormones immunostainings for the transcription factors have to be examined. If these are also negative the criteria for an endocrine inactive null cell adenoma are fulfilled. If one transcription factor is positive the corresponding cell lineage indicates a potential hormonal activity of the adenoma. So Pit-1 expressing hormone-negative adenomas can account for acromegaly, hyperprolactinemia, or TSH hyperfunction. T-pit positive hormone negative adenomas can induce Cushing’s disease, and SF-1 positive hormone negative tumors indicate gonadotrophic adenomas. Instead of the deleted atypical adenoma of the WHO classification of 2004 now (WHO classification 2017) criteria exist for the identification of aggressive adenomas with a conceivably worse prognosis. Some adenoma subtypes are described as aggressive “per se” without necessity of increased morphological signs of proliferation. All other adenoma subtypes must also be designated as aggressive if they show signs of increased proliferation (mitoses, Ki-67 index>3–5%, clinically rapid tumor growth) and invasion. By these criteria about one third of pituitary adenoma belong to the group of aggressive adenomas with potentially worse prognosis. The very rare pituitary carcinoma (0.1 % of pituitary tumors) is defined only by metastases. Many of them develop after several recurrences of Prolactin or ACTH secreting adenomas. The correlation of clinical findings and histological classification of pituitary adenomas is very important since every discrepancy has to be discussed between clinicians and pathologists. Based on data of the German Registry of Pituitary Tumors a table for examinations of correlations is shown in this review.